Antiimperialism a guide for the movement (Bookmarks, 2003)
"A mass movement against war has swept across the globe. It has sparked new debates and questions about imperialism in the 21st century. Anti-Imperialism brings together some of the leading activists and writers in the anti-war movement to look at the issues, main players and regions most affected by imperialism past and present. This handbook is essential reading for activists everywhere."--BOOK JACKET.